Centrifuge model study on the seismic responses of shield tunnel. (October 2019) - Wang, Jie; Liu, Hongqing; Liu, Huabei; Zou, Yan
Highlights: Centrifuge shaking-table tests were conducted on shield tunnel models. Effects of vertical motion and segmental lining were investigated. Vertical excitation modified the propagation of the horizontal seismic motion. Tunnel seismic responses were considerably influenced by vertical excitation. Dynamic soil-structure interaction was considerably influenced by segmental lining. Abstract: A series of centrifuge shaking-table tests were carried out to investigate the seismic responses of shield tunnels in dry sand. Both horizontal and horizontal plus vertical seismic excitations were considered in the tests. Shield tunnel models consisting of segments connected by bolts were employed, and continuous tubes were used as a comparison in the testing program. The results showed that the dynamic bending moments of the tunnel models were significantly influenced by the input seismic excitations and the type of tunnel models. Vertical seismic excitation might considerably increase the dynamic bending moments in the lining, and the segmental models had different moment distributions from the continuous ones. The joint opening displacements of the segment tunnel models, the ground accelerations and the earth pressures were also measured in the centrifuge shaking table tests, which further highlight the influences of the vertical excitations and the segmental characteristics of shield tunnel linings.